2011
DOI: 10.1038/leu.2010.310
|View full text |Cite
|
Sign up to set email alerts
|

Human but not murine multipotent mesenchymal stromal cells exhibit broad-spectrum antimicrobial effector function mediated by indoleamine 2,3-dioxygenase

Abstract: Human multipotent mesenchymal stromal cells (MSCs) exhibit multilineage differentiation potential, support hematopoiesis, and inhibit proliferation and effector function of various immune cells. On the basis of these properties, MSC are currently under clinical investigation in a range of therapeutic applications including tissue repair and immune-mediated disorders such as graft-versus-host-disease refractory to pharmacological immunosuppression. Although initial clinical results appear promising, there are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
214
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(233 citation statements)
references
References 31 publications
10
214
1
6
Order By: Relevance
“…In mice, MSCs rely on nitric oxide (NO) produced by iNOS to protect themselves (9). Interestingly, we found that the expression of iNOS (NOS2) and human IRG genes was close to zero in MSCs both before and after stimulation with IFN-γ, which was also the case for the constitutive NOS (NOS1 and NOS3) genes, further supporting the notion that iNOS shows no increase in expression after stimulation.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…In mice, MSCs rely on nitric oxide (NO) produced by iNOS to protect themselves (9). Interestingly, we found that the expression of iNOS (NOS2) and human IRG genes was close to zero in MSCs both before and after stimulation with IFN-γ, which was also the case for the constitutive NOS (NOS1 and NOS3) genes, further supporting the notion that iNOS shows no increase in expression after stimulation.…”
Section: Resultssupporting
confidence: 70%
“…2D, siRNAmediated IDO knockdown also could not rescue the parasite from IFN-γ-mediated growth inhibition. These results suggest that the ability of human MSCs inhibiting the growth of T. gondii does not depend on Trp deprivation or IDO activity, which is in contrast to the results presented from a previously reported study (9).…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…For example, hMSCs, but not mMSCs, possess antimicrobial properties against a range of clinically relevant bacteria through their ability to up-regulate the expression of indoleamine 2,3-dioxygenase [68]. Additionally, mMSCs, but not hMSCs, express inducible nitric oxide synthase [68], and it has been shown that hMSCs and mMSCs express different mMSC lysates were analyzed by western blot. P-Akt quantities relative to Akt were measured based on optical densities of the gel bands, and normalized to that of hypoxia control (n = 4).…”
Section: Discussionmentioning
confidence: 99%